The Use Of Pictured Comic父与子 [Fù Yǔ Zi] to Practice The Mandarin Reading Skills Of Grade X Students Of SMAN 2 Kota Malang - Restiana Putri Wulandari; Karina Fefi Laksana Sakti; Sawitri Retnantiti (Journal of Chinese Language and Culture Studies, 2026)
The ability to master foreign languages is essential in the globalization era, and Mandarin is one of the most widely spoken languages in the world. However, many high school students in Indonesia still experience difficulties in reading Mandarin texts, particularly in recognizing pinyin, hanzi, and comprehending the meaning of a passage. This study aimed to explore the use of the illustrated comic 父与子 [Fù yǔ zi] as a learning medium to improve students’ reading skills in Mandarin. A descriptive qualitative approach was employed, with research conducted at SMAN 2 Malang involving grade X students as participants. Data were collected through classroom observations and questionnaires, supported by validated instruments consisting of observation sheets and response forms. The findings revealed that the use of 父与子 comics facilitated students in understanding main ideas, identifying character relations, recognizing humor, and grasping moral messages in the stories. The short and simple dialogues in the comic also helped students to learn new vocabulary and retell the story more easily, while the illustrations created a more engaging and interactive classroom atmosphere. Questionnaire results further confirmed positive student responses, as the majority reported increased interest, motivation, and comprehension when learning through comics. In conclusion, the 父与子 comic proved to be an effective and enjoyable medium for teaching Mandarin reading skills, with significant contributions to vocabulary enrichment and learning motivation. The study recommends teachers to apply comics as alternative reading materials, while future research may expand the scope by comparing with other visual media and exploring speaking and writing skills.